Factors Influencing U.S. Consumers' Preference for Positively Versus Negatively Framed GM Food Symbols. Issue 1 (2nd January 2018) - Rodriguez, Lulu; Kulpavaropas, Supathida
ABSTRACT: This study explores the factors that may have a bearing on consumers' preference for positively and negatively framed symbols on food products containing genetically modified ingredients. An online survey tested the influence of three categories of variables—individual cognitive-psychological attributes, media and information-related variables, and demographic characteristics—on consumers' preference for symbols that have been framed in a positive or negative way. The findings indicated that consumers' preference for positively framed symbols was determined by their objective knowledge of genetic modification, education, and income, while preference for negatively framed symbols was influenced by objective knowledge and exposure to food labels.